心算教學活動實踐於小一數學課室之研究 Mental Computation Activity Implementation into First-Grade Mathematics Classes - 楊德清 Der-Ching Yang; 黃瓊賢 Cyong-Slan Huang (National Taiwan Normal University, 2012)
本研究採質性研究法探討國小一年級學生進行心算教學活動之成效、策略改變情形及教學活動的實施歷程。研究樣本為實驗組學生21 人，進行二位數加減一位數的心算策略教學。對照組學生16人，依照教科書規劃的方式進行二位數加減一位數的教學，兩班各進行12 節課教學。研究結果顯示：教學後實驗組學生在心算之表現顯著優於對照組學生。同時，結果亦顯示教學後實驗組學生能夠發展多元之解題策略，如分離策略、集合策略，以及整體策略等。相反地，對照組學生在教學前、後，所使用之策略以數數策略、圖像與直式心像為主，改變較少，且少有心算策略的使用。教學過程中，藉由高分組學生的回答帶動中分組與低分組學生的思考，同時學生對於能夠上臺分享自己的策略感到興奮。最後根據研究結果，針對心算教學活動融入一年級數學課程及未來研究提出建議。 This study employs a qualitative approach to investigate the effect of mental computation activities integrated into first-grade mathematics classes. The mental computation activities, including 2-digit addition and subtraction problems, were used in an experimental group comprising 21 students. The control group comprised 16 students who were following textbook activities, including 2-digit addition and subtraction problems. The teaching intervention lasted for 12 periods for both groups. The results show that students in the experimental group experienced improved performance for mental computation than students in the control group following intervention. Additionally, data indicate that students in the experimental group can develop and use multiple mental strategies, such as separation, aggregation, and holistic strategies following intervention. Conversely, students in the control group preferred using counting and pictorial strategies, as well as images of written computation. Fewer mental strategies were used in the control group. During the instruction of mental computation, students' problem-solving ability in the mid- and low-level can be improved by high-level students' explanations. The teaching, learning, and curriculum design of mental computation, as well as directions for future studies, are discussed.